The Political Influence of US and China Vaccine Competition in Southeast Asia on Potential New Security Issues for ASEAN Countries - Saputra, Oddie Bagus; Larasati, Ria Agustina (Institute of Social and Political Science Jakarta (Institut Ilmu Sosial dan Ilmu Politik Jakarta - IISIP Jakarta), 2023)
Vaccine competition between the United States and China in Southeast Asia has been potential to create new security problems for ASEAN member states. Based on the constructivism perspective and Regional Security Complex Theory (RSC), this article analyses the relationships between the identity and interest of both states, US and China, who took certain policies and engaged in the vaccine competition in the Southeast Asian region. China with the political manoeuvre and US with the humanitarian endeavour in their narration, both had interests in terms of economic, politics, also geopolitics through their assistance to ASEAN countries. The authors argue that new security problems, such as the rising unemployment rates, the declining GDP, and the new pandemic wave, caused by this competition are the result of the absence of collective identity of ASEAN countries. Instead of prioritizing their collective identity as a regional community and forming regional security complex, ASEAN countries tend to respond by prioritizing their respective national interests. Therefore, this article offers the recipes where ASEAN member state should establish their collective identity, such as supporting the development of ASEAN vaccines in Vietnam and Thailand or establishing the ASEAN pharmaceutical company designates as the regional vaccine research and development site.